Influence of pH in the enzymatic hydrolyzate of concentrates from the fishmeal industry - Corral Palacios, Jairo; Delgado-Demera, María Hipatia; Cedeño-Palacios, Carlos Alfredo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The fishmeal concentrate is a byproduct that has an important amount of components useful for the food industry. However, if the fishmeal concentrate is not processed, it could cause an imbalance of the environment in which the waste is discharged. The aim of this research was to evaluate the influence of the pH in the enzymatic hydrolysis of the fishmeal industry for the production of protein concentrates from stickwater as a primary commodity. Thus, the pH values (5,32; 5,94 y 6,33) were examinated, also a proximal analysis to hydrolysate and soluble fish was carried out. In order to determine protein, moisture, fats and ashes the following methods were used, Kjeldhal method for protein, rapid thermobalance method for moisture, Soxhlet methos for fats, and official INEN 0467 method for ashes. Protein concentration analyzes were performed by the Bradford method, and subsequently, the hydrolysis approximation was calculated and the amino acid composition was determined by the reference method Waters UPLC. The results showed that the pH of 6.33 allowed to achieve a better hydrolysis because a higher hydrolysis approximation was obtained, thus also the results obtained from the amino acid composition in the final product demonstrate its potential use as a food additive.